Polydimethylsiloxane Composites for Optical Ultrasound Generation and Multimodality Imaging. (15th January 2018) - Noimark, Sacha; Colchester, Richard J.; Poduval, Radhika K.; Maneas, Efthymios; Alles, Erwin J.; Zhao, Tianrui; Zhang, Edward Z.; Ashworth, Michael; Tsolaki, Elena; Chester, Adrian H.; Latif, Najma; Bertazzo, Sergio; et al.
Abstract: Polydimethylsiloxane (PDMS) is widely used in biomedical science and can form composites that have broad applicability. One promising application where PDMS composites offer several advantages is optical ultrasound generation via the photoacoustic effect. Here, methods to create these PDMS composites are reviewed and classified. It is highlighted how the composites can be applied to a range of substrates, from micrometer‐scale, temperature‐sensitive optical fibers to centimeter‐scale curved and planar surfaces. The resulting composites have enabled all‐optical ultrasound imaging of biological tissues both ex vivo and in vivo, with high spatial resolution and with clinically relevant contrast. In addition, the first 3D all‐optical pulse‐echo ultrasound imaging of ex vivo human tissue, using a PDMS‐multiwalled carbon nanotube composite and a fiber‐optic ultrasound receiver, is presented. Gold nanoparticle‐PDMS and crystal violet‐PDMS composites with prominent absorption at one wavelength range for pulse‐echo ultrasound imaging and transmission at a second wavelength range for photoacoustic imaging are also presented. Using these devices, images of diseased human vascular tissue with both structural and molecular contrast are obtained. With a broader perspective, literature on recent advances in PDMS microfabrication from different fields is highlighted, and methods for incorporating them into new generations of optical ultrasound generators are suggested. Abstract : Polydimethylsiloxane (PDMS) composites offer several advantages for optical ultrasound generation via the photoacoustic effect. Here, methods to fabricate PDMS composites are reviewed and their application to substrates of varying sizes and geometries is highlighted. It is demonstrated that certain PDMS composites enable both all‐optical ultrasound and photoacoustic imaging of biological tissue with high spatial resolution and clinically relevant contrast.